Penerapan Prinsip-Prinsip Good Corporate Governance dan Implikasinya terhadap Kinerja Karyawan Pusat Gadai Indonesia di Kabupaten Subang - Rio Devlin Pahlevi Carnadinata; Asnita Frida Sebayang (UNISBA Press, 2024)
Abstrack. Awareness of the importance of Good Corporate Governance increases along with growing discussions among the community, stakeholders, government and company management. They realize the need for an effective system to improve Transparency, Accountability, Responsibility, Independence and Fairness. The principles of Good Corporate Governance are the main focus in creating positive economic conditions for all parties, both in public and private companies. This study aims to examine and determine the Application of Good Corporate Governance Principles to Employee Performance based on the perspective of employees of the Indonesian Pawn Center in Subang Regency. The research method uses Non-Probability Sampling Type with a sample size of 61 respondents who are employees of the company. Data analysis was carried out using Likert scale analysis with the help of SPSS Version 25 software. The results of the validity test and reliability test show valid and reliable results. The results of the analysis show that the Indonesian Pawn Center Company has implemented the principles of Good Corporate Governance very well. Based on the research results obtained, the strongest instruments are the Principles of Independence (X4) with an average score of 102.2, then Transparency (X1) with an average score of 102, Employee Performance (Y) with an average score of 101.9, Principles Fairness (X5) with an average score of 101.2, Principles of Responsibility (X3) with an average score of 101.1 and finally the weakest is Accountability (X2) with an average score of 100. Abstrak. Kesadaran akan pentingnya Good Corporate Governance meningkat seiring dengan diskusi yang berkembang di kalangan masyarakat, stakeholder, pemerintah, dan manajemen perusahaan. Mereka menyadari kebutuhan sistem yang efektif untuk meningkatkan transparansi, akuntabilitas, tanggungjawab, kemandirian, dan kewajaran. Prinsip-prinsip Good Corporate Governance menjadi fokus utama dalam menciptakan kondisi ekonomi yang positif bagi semua pihak, baik di perusahaan publik maupun swasta. Penelitian ini bertujuan untuk mengkaji dan mengetahui penerapan prinsip-prinsip Good Corporate Governance terhadap kinerja karyawan berdasarkan perspektif karyawan Pusat Gadai Indonesia di Kabupaten Subang. Metode penelitian menggunakan Jenis Non-Probability Sampling dengan jumlah sampel sebanyak 61 responden yang merupakan Karyawan Perusahaan tersebut. Analisis data dilakukan menggunakan analisis skala likert dengan bantuan perangkat lunak SPSS Versi 25. Hasil uji validitas dan uji reliabilitas menunjukan hasil yang valid dan reliabel. Hasil analisis menunjukkan bahwa Perusahaan Pusat Gadai Indonesia telah menerapkan prinsip-prinsip Good Corporate Governance dengan sangat baik. Berdasarkan hasil penelitian yang diperoleh, instrumen terkuat yaitu pada prinsip kemandirian (X4) dengan skor rata-rata 102,2 kemudian transparansi (X1) dengan skor rata-rata 102, kinerja karyawan (Y) dengan skor rata-rata 101,9, prinsip kewajaran (X5) dengan skor rata-rata 101,2, prinsip tanggungjawab (X3) dengan skor rata-rata 101,1 dan terakhir yang paling lemah yaitu akuntabilitas (X2) dengan skor rata-rata 100.